In Vitro Study of the Toxicity Mechanisms of Nanoscale Zero-Valent Iron (nZVI) and Released Iron Ions Using Earthworm Cells - Jaroslav Semerad; Natividad Isabel Navarro Pacheco; Alena Grasserova; Petra Prochazkova; Martin Pivokonsky; Lenka Pivokonska; Tomas Cajthaml (Nanomaterials, 2020)
During the last two decades, nanomaterials based on nanoscale zero-valent iron (nZVI) have ranked among the most utilized remediation technologies for soil and groundwater cleanup. The high reduction capacity of elemental iron (Fe0) allows for the rapid and cost-efficient degradation or transformation of many organic and inorganic pollutants. Although worldwide real and pilot applications show promising results, the effects of nZVI on exposed living organisms are still not well explored. The majority of the recent studies examined toxicity to microbes and to a lesser extent to other organisms that could also be exposed to nZVI via nanoremediation applications. In this work, a novel approach using amoebocytes, the immune effector cells of the earthworm Eisenia andrei, was applied to study the toxicity mechanisms of nZVI. The toxicity of the dissolved iron released during exposure was studied to evaluate the effect of nZVI aging with regard to toxicity and to assess the true environmental risks. The impact of nZVI and associated iron ions was studied in vitro on the subcellular level using different toxicological approaches, such as short-term immunological responses and oxidative stress. The results revealed an increase in reactive oxygen species production following nZVI exposure, as well as a dose-dependent increase in lipid peroxidation. Programmed cell death (apoptosis) and necrosis were detected upon exposure to ferric and ferrous ions, although no lethal effects were observed at environmentally relevant nZVI concentrations. The decreased phagocytic activity further confirmed sublethal adverse effects, even after short-term exposure to ferric and ferrous iron. Detection of sublethal effects, including changes in oxidative stress-related markers such as reactive oxygen species and malondialdehyde production revealed that nZVI had minimal impacts on exposed earthworm cells. In comparison to other works, this study provides more details regarding the effects of the individual iron forms associated with nZVI aging and the cell toxicity effects on the specific earthworms’ immune cells that represent a suitable model for nanomaterial testing.